Command, control and co-creation - Vrbek, Sanja (Central European Public Administration Review, 2022)
The academic contribution to the field is twofold. Firstly, the paper identifies co-creation drivers and barriers from the professionals’ point of view ? a largely overlooked perspective in the relevant literature. Secondly, by being placed in the Slovenian administrative context, the paper complements and enriches the debate on co-creation shaped predominantly by the experience of Northern and Western Europe. Purpose: By focusing on the Slovenian public sector, as a traditionally hierarchical administrative context, the paper aims to identify factors that stimulate professionals to implement co-creation in their everyday work, as well as factors that impede their decision and behaviour in this direction. Design/methodology/approach: The paper relies on two Slovenian case studies capturing the experience of professionals from the Ministry of Public Administration and the Municipality of Ljubljana. The key data-gathering methods were qualitative open-ended interviews with ‘lead professionals’ (at managerial positions) and focus groups with professionals who have regular contact with service users/external stakeholders and/or experience with co-creation. Findings: The findings of the paper indicate that professionals implement co-creation even in ‘unfavourable’ hierarchical and centralised settings. A key driver for them to co-create in such a context is strong political support at the highest level. However, a more profound internalisation of co-creation depends on the redefinition of their professional identity, as well as on the (personal or collective/organisational) interest in co-creation. Originality/significance: The paper makes a pioneer step in providing an in-depth look into the drivers and barriers professionals face when implementing co-creation in the Slovenian public sector. As such, it provides valuable input for further comparative analyses of co-creation drivers and barriers faced by professionals across Central and Eastern Europe.
Keywords: barriers; co-creation; drivers; javni uslužbenci; ovire; professionals; Slovenia; Slovenija; soustvarjanje; spodbudni dejavniki